ANALISIS SURFACE HARDNESS ALUMINUM 6061 HASIL GAS NITRIDING DENGAN VARIASI HOLDING TIME - Oerbandono, Tjuk (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The nitriding coating process is widely applied in the industry. Gas nitriding is a technique used to improve the mechanical properties of a metal. This study aims to determine the influence of holding time variations on surface hardness and diffusion depth in aluminum alloy 6061 (Al-Mg-Si) that undergoes gas nitriding. The independent variable used in this study was holding time, namely, initial specimen (without holding time treatment), and specimens that experienced holding ranging from 1 hour, 2 hours, 3 hours, 4 hours, and 5 hours. The cooling medium used after gas nitriding was air. The highest surface hardness value was obtained in aluminum alloy 6061 specimens without holding time treatment, namely with a hardness value of 141 VHN while the lowest surface hardness value was produced by the specimen with a holding time of 5 hours. The lowest surface hardness value was 55.4 VHN. Based on the results of the EDAX composition test known that the specimen of aluminum alloy 6061 with a holding time of 5 hours diffused nitrogen element of 1.57% and oxygen element of 5.27%.